Effects of Tai Chi Chuan practice on sleep quality - Jiménez, Pedro Jesús (Revista de Artes Marciales Asiáticas, 2012)
Aim: This paper reviews international studies on the effects of Tai Chi Chuan (a.k.a. taichi, taiji or taijiquan) on sleep with the aim of clarifying the research framework, which are its causes and effects. Method: The literature search was carried out on the basis of seven international databases on October 2011. Results/Conclusions: The review works on the subject are scarce and address a small number of studies, while specific works confirm that tai chi chuan produces a significant improvement over the stability (sleep disruption) and quality (efficacy and duration) of nighttime sleep, and an overall improvement on daytime sleep, although to enjoy these benefits its required a minimum of practice. The physiological causes that lead to this improvement are still to be determined.